The politics of citation: An analysis of doctoral theses across the disciplines - Afful, Joseph Benjamin Archibald; Janks, Hilary (My University, 2013)
Citation is used as a measure to rank academics and institutions on the assumption that the more one is cited, the greater the impact of one’s research. For this reason, citations in high impact journals that appear on highly regarded scientific indices are favoured as sites for publishing one’s work. There can be no doubt that citation in the academy is a politicized practice. In acquiring advanced academic literacy, students have to master the art of positioning themselves in relation to the work of others, so that they develop their own ‘scholarly identity’. Drawing on insights from sociology of knowledge, information science, and critical discourse analysis, in this paper, we examine the reference lists of ten doctoral theses, from three disciplines – Animal, Plant and Environmental Sciences, Literature, and Sociology – in a leading South African university. Four parameters: (1) authorship (2) type of source (3) place of publication and (4) date of publication are used as means of understanding differences in relation to knowledge construction across the different disciplines. The analysis of the reference lists shows that they are a highly politicized discursive site marked by particular values, alliances, allegiances, and dominant forms that are privileged. The findings from this study have important implications for advanced academic literacy, disciplinary discourse studies at doctoral level, and postgraduate supervision.
Keywords: Citation rates in academia; Doctoral theses -- ranking by means of citation